Genomic analysis of putative hybrids between Potamochoerus spp. and domestic pigs from sympatric areas in West Africa and Madagascar - Rianja Rakotoarivony; Nicolas Mary; Farid Bahleman; Jörg Beckmann; Sandra Blome; Virginia Friedrichs; Horst Oebel; Hélène Jourdan-Pineau; Anjaranirina Marcel Mamiarisoa; Vincent Michaud; Johan Michaux; Christopher L. Netherton; et al. (PLoS ONE, 2026)
In many rural areas of sub-Saharan Africa and Madagascar, domestic pigs (DPs, Sus scrofa domesticus ) can coexist in sympatry, with species of the genus Potamochoerus spp. ( P. larvatus or P. porcus ). Reports of hybridization between domestic pigs and these two wild suid species are common in these areas. However, the existence and level of genetic introgression of those hybrids has never been sufficiently investigated to date to provide tangible conclusions on the occurrence of such interspecific hybridizations. The aim of our research was to investigate the genomic introgression of suspected hybrids following reported cross breeding events between DPs and P. porcus and P. larvatus in Benin and Madagascar, respectively. A total of 75 samples of individuals representing Sus scrofa domesticus (n = 32), P. larvatus (n = 7), P. porcus (n = 17) and putative hybrids (n = 19) were collected from the field and from European zoos. After filtering, 55 samples passed quality control and were retained for subsequent genotype analysis using 70K SNPs chip. The resulting genomic data was compared by principal component and admixture analysis. Our results revealed the absence of genetic introgression of Potamochoerus spp. in the selected putative hybrids. To further investigate these findings, we expanded our analyses to a global population of Sus scrofa , with the aim of identifying variations in their ancestral origins (Asian or European). These analyses revealed that the suspected hybrids from Madagascar and local DPs are derived from crosses between European and Asian DP populations, with proportions of 34% and 66%, respectively. In contrast, Beninese hybrids derived exclusively from European suids. This study provides, to our knowledge, the most comprehensive assessment to date of potential hybridization between DP and Potamochoerus spp. in sub-Saharan Africa. The great variability of local DP populations (European and Asian) may explain the presence of unique phenotypes when these distinct lineages are crossed, which may be falsely identified as hybrids between DP and Potamochoerus spp., if based on phenotypic data alone.